2020
DOI: 10.1002/osp4.405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel combination of orlistat and acarbose on tolerability, appetite, and glucose metabolism in persons with obesity

Abstract: Objective: There is an unmet medical need for a safe and effective weight loss product with minimal systemic side-effects. In this study, the effect of a novel modified-release fixed-dose combination of orlistat and acarbose (MR-OA) was compared with conventional orlistat (CO) regarding tolerability, appetite and glucose metabolism.Methods: Sixty-seven men with obesity, aged 24 to 60 years with body mass indexes (BMIs) 33 to 40 kg m −2 or BMIs 30 to 32 kg m −2 and waist circumference above 102 cm were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
4
22
0
1
Order By: Relevance
“…16 Acarbose plasma concentrations are difficult to measure due to a lack of ionized functional chemical groups within the molecule; therefore, bioequivalence in glucose-lowering capability is the usual way of determining an acarbose effect. 18,19 In the previous study, 5 we showed an expected effect on plasma glucose concentration, which was similar to that reported with conventional oral product of acarbose, 20 a sign that the MR-OA formulation does not affect acarbose absorption.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…16 Acarbose plasma concentrations are difficult to measure due to a lack of ionized functional chemical groups within the molecule; therefore, bioequivalence in glucose-lowering capability is the usual way of determining an acarbose effect. 18,19 In the previous study, 5 we showed an expected effect on plasma glucose concentration, which was similar to that reported with conventional oral product of acarbose, 20 a sign that the MR-OA formulation does not affect acarbose absorption.…”
Section: Discussionsupporting
confidence: 89%
“…These 3 dose strengths were given to the 3 treatment groups; group I, II, and III, respectively, a conventional orlistat product, that is, Xenical, 120 mg was used as comparator (Table 1), denoted in group IV. A detailed description of the study was published previously 5 . Ethics approval was granted by the regional Ethical Review Board in Uppsala, Sweden (dnr 2016/257).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations